The observed difference of RAW264.7 macrophage phenotype on mineralized collagen and hydroxyapatite. (11th April 2018) - Shi, Xiu-Di; Chen, Li-Wei; Li, Si-Wen; Sun, Xiao-Dan; Cui, Fu-Zhai; Ma, Hong-Mei
Abstract: Understanding the interaction between biomaterials and the immune system has become increasingly important. Mineralized collagen (MC) has the same chemical components and microstructures to natural bone tissue, and is considered as a better biomaterial for bone prostheses compared to hydroxyapatite (HA). However, there is little information about how MC affects inflammatory responses. In this study, we investigate the inflammatory responses to MC and HA by culturing RAW264.7 cells on their surfaces. We observed that MC increases CD206+ staining and IL-10 (M2 macrophages), whereas HA shows cells expressing more CD86 and secreting more TNF- α . This result indicates that MC may attenuate inflammatory responses to implanted bone prostheses.